Inclusive education in the academy: pedagogical and political imperatives in a master’s course - Walton, Elizabeth (Taylor & Francis, 2018)
Many universities offer undergraduate and postgraduate courses in inclusive education. There has been much research into the impact of these courses, but little is written about their design. This article focuses on a master’s course in inclusive education in a South African university. The course positions inclusive education as a critical education project and is designed around the four propositions presented by Slee in The Irregular School (2011. Milton Park: Routledge). Using Bernsteinian ideas about pedagogising knowledge, this article accounts for the pedagogical choices made in content selection and course design. The focal questions in the course are described, together with an indication of the range of additional texts that students read. Given that Slee asserts that inclusive education is a political project, and that Allan (2010. “The Inclusive Teacher Educator: Spaces for Civic Engagement.” Discourse: Studies in the Cultural Politics of Education 31 (4): 411–422) urges inclusive teacher educators to reorientate themselves towards civic duty, I argue that producing a pedagogic discourse of inclusive education is a political task that should result in both the teacher educator and the students being oriented towards a critique of existing exclusionary arrangements and an activism that leads to change.